Wounding-induced redirection of sugar transport fuels tissue repair - Rotem Matosevich; Mika Della Zuana; Itay Cohen; Idan Efroni (Proceedings of the National Academy of Sciences, 2026)
Wounding triggers growth programs to restore damaged tissues, creating a local surge in metabolic demand. How resource recruitment is modified to meet this demand is unclear. Here, we show that regeneration of dissected root tips is dependent on photosynthetic sucrose in a dose-dependent manner, although sucrose itself is excluded from the injury site. High-resolution tracking of Glifon, a live glucose reporter, reveals that glucose accumulates near the cut. Glucose accumulation required the apoplasmic sugar transport components CELL WALL INVERTASE ( CWINV ) and SUGAR TRANSPORTER PROTEINS ( STP ), which were rapidly induced by wounding. Loss of CWINV or STP function compromised root repair, particularly under limited sucrose availability, whereas increased STP13 gene dosage enhanced repair rates. Similar sugar transport genes were activated in other wounding contexts and promoted wound-induced adventitious root initiation. We propose that injury elicits a proactive local shift in sugar flow to promote resource recruitment and sustain tissue repair.